THE EFFECT OF PERCEIVED PRICE, PROMOTION, PRODUCT QUALITY AND SERVICE QUALITY ON CONSUMER PURCHASE INTENTIONS LAZADA MARKETPLACE IN DEPOK - Eulin Karlina; Instianti Elyana; Fera Nelfianti; Siti Nuryati; Zaenal Arief (SEAN Institute, 2023)
In today's modern era, acceleration and innovation in technology are pushing the world economy forward, so many new startups have sprung up that have come up with ideas to raise the level of the economy, such as online shops, e-commerce, and others. Lazada is a marketplace that is in demand by various groups for online transactions by often offering promotional programs at lower prices with free shipping and good service. This study aims to determine the effect of perceived price, promotion, product quality, and service quality in the Lazada marketplace on consumer purchasing decisions in Depok. This study uses a quantitative descriptive method by distributing questionnaires through Google Forms with purposive sampling, namely Lazada users as a consumer online shopping platform in Depok. In analyzing the data, this study used SPSS 26 to calculate the results of the Multiple Linear Regression variable test, t-test, F test, and determination analysis. The results of this study indicate that based on the t-test, price perceptions have a positive and insignificant effect on purchasing decisions, and based on the t-test, promotion and product quality have a positive and significant effect on purchasing decisions. Based on the results of the F test, perceptions of price, promotion, product quality, and service quality significantly affect consumers' purchasing decisions in Depok. Based on the results of multiple regression analysis, the effect of perceived price, promotion, product quality, and service quality on purchasing decisions is only 73.5%. The remaining 26.5% is influenced by other variables not examined in this study.